2018
DOI: 10.1007/s00436-018-5971-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of vector-borne parasites in wild micromammals, Barcelona (Spain)

Abstract: Information about the role of micromammals in the epidemiology of Leishmania infantum and Babesia sp. in southern Europe is scarce. Wild micromammals were captured in natural areas in the Barcelona province (NE Spain) in 2011 and analysed by real-time PCR for the presence of DNA of Piroplasmida (n = 253) and Leishmania infantum (n = 166). The wood mouse (Apodemus sylvaticus) was the most abundant species, but all specimens tested negative for L. infantum, for which two out of 15 (13.3%) white-toothed shrews (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the last 25 years, the possible role of rodents in the L. infantum cycle has been assessed in nine countries of the Mediterranean basin, with the highest number of studies being carried out in Iran. Seven studies were performed in more than one of these nine countries (11,14,25,41,44,45,52) (Figure 1B). If the Mediterranean basin is divided into three large geographical areas, Southern Europe, North Africa and the Middle East, the latter concentrates the greatest number of studies (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…In the last 25 years, the possible role of rodents in the L. infantum cycle has been assessed in nine countries of the Mediterranean basin, with the highest number of studies being carried out in Iran. Seven studies were performed in more than one of these nine countries (11,14,25,41,44,45,52) (Figure 1B). If the Mediterranean basin is divided into three large geographical areas, Southern Europe, North Africa and the Middle East, the latter concentrates the greatest number of studies (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…In Spain, and in addition to domestic dogs, leporids such as rabbits and hares have been demonstrated to be competent reservoirs of the infection (Ortega‐García et al., 2019). Micromammals have been largely believed to play a limited role in the epidemiology of the parasite (Millán, 2018). This concept has been recently challenged by the finding of L. infantum at a high prevalence rate (33%, 28/84) in sewer rats captured in the city of Barcelona (Galán‐Puchades et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Micromammals have been largely believed to play a limited role in the epidemiology of the parasite (Millán, 2018). This concept has been recently challenged by the finding of L. infantum at a high prevalence rate (33%, 28/84) in sewer rats captured in the city of Barcelona infantum in a previous Spanish study (Risueño et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Two different PCR techniques facilitate detection of the parasite (Navea-Pérez et al, 2015;Tsakmakidis et al, 2017). Regarding rodents of the genus Mus, L. infantum has been found in M. musculus specimens in Portugal (10 of 27, 37.0%), Spain (2 of 4, 50.0%) and Greece (16 of 67, 23.9%) (Helhazar et al, 2013;Navea-Pérez et al, 2015;Tsakmakidis et al, 2017), but the parasite has only been found in one M. spretus specimen (4.3% infection prevalence) (Millán, 2018). A comparatively higher prevalence of L. infantum was observed in M. musculus captured in the vicinity of the patient diagnosed with leishmaniasis in the present study (16 of 18, 88.9%).…”
Section: Re Sults and Discussionmentioning
confidence: 99%